'Een schadelijke instelling'. Kritiek op het parlement in België in het interbellum - Gerard, E. (BMGN - Low Countries Historical Review, 2005)
A harmful institution. Critique of the Belgian parliament during the interwar periodTwo key features that characterise the interwar period are the crisis within the parliamentary system and the rise of fascism. The wave of criticism directed at the Belgian parliament can be attributed to this overall climate, although it also has its own peculiarities that originate from Belgian’s political culture, particularly its strong parliamentary tradition. The First World War acted as a catalyst for this strong antiparliamentary critique through the outburst of nationalism and the cult of violence it unleashed along with the temporary suspension of parliamentary activity and the concomitant process of democratisation. The criticism that had been confined to extremist groups from both the left and the right during the 1920s reached a crescendo and became endemic after 1933, particularly among the younger generations. Abuse of power, acting as a front for shady practices, unable to deal with economic issues, disrupting national unity, unrepresentative, and mediocre MPs; these were just some of the recurring themes in the anti-parliamentary debate, which was not so much the result of carefully balanced arguments as the reflection of a popular trend. The Belgian parliament acknowledged its shortcomings, but was unable to turn back the tide. The scope of the anti-parliamentary criticism can be measured by the power shift at the end of the 1930s which favoured the monarchy at the expense of parliament. This article is part of the special issue 'Parlementen in de Nederlanden'.